마늘의 생육자료와 기상자료 기반으로 다층모형을 이용한 수확기 구중 추정 - 최성천(Seong Cheon Choi); 김준기(Jun Ki Kim); 서홍석(Hong Seok Seo) (Weon'ye gwahag gi'sulji, 2021)
마늘은 노지 작물로 기상에 따라 작황 변동성이 크기 때문에 생산량과 가격의 불안정성이 크다. 안정된 수급관리를 위하여정확한 생산량 예측이 선제적으로 이루어져야 한다. 본 연구는 구 비대 초기의 마늘 생육과 기상자료를 기반으로 구중 추정모형을 개발함으로써 생산량 예측의 정확도 개선을 도모하였다. 분석은 개체단위인 4월 하순 지상부 생육자료와 필지단위인 4월하순에서 수확기까지 기상 추정자료로 구성된 위계적자료 특성을 반영하여 2-수준 다층모형을 활용하였다. 분석결과 4월 하순 엽초경, 초장의 생육이 좋을수록 생구 무게가 증가하는 것으로 나타났다. 기상은 강수량, 강우일수는 구중에 감소효과를, 수확직전 강수량, 일조시간, 증발산량, 최적기온일수는 증가효과가 나타나 마늘 최종 구중에 유의한 요인으로 확인되었다. There is a large fluctuation in the production and price of garlic (Allium sativum L.) because it isgrown mainly in the open field and is vulnerable to weather conditions. Accurate forecasting isneeded to manage production. The purpose of this study was to improve the accuracy of productionforecasting by developing a model that estimates the weight of garlic bulbs at harvest based ongrowth and meteorological data. For this study, a two-level multilevel model was used to reflect thehierarchical data characteristics consisting of individual unit data that represented the above-groundgrowth conditions at the end of April and the lot unit data that represented the meteorologicalconditions from the end of April to harvest time. It was determined that the weight of the garlic bulbincreased as the growth of the sheath diameter and the plant height increased at the end of April. Asfor the meteorological factors, it was estimated that precipitation had negative effects on the garlicbulb weight, while the pre-harvest precipitation, duration of sunshine, evapotranspiration, and theoptimal temperature days had positive effects on the weight. KCI Citation Count: 8